Primary Pulmonary Nocardiosis: A Case Report (Iraqi Journal of Medical Sciences, 2016)
A 28-year-old non smoker male who had undergone kidney transplantation and has been taking immunosuppressive drug for the last 15 months was presented to the Hospital of Special Surgery/Baghdad with low grade fever, productive cough, shortness of breath, purulent sputum and bilateral chest crepitation. Laboratory investigations showed low Hb percentage (11.9%) with normal blood urea and creatinine (42 mg/ dL and 0.9 mg/ dL respectively). Chest x-ray revealed homogenous shadow. Initial antibiotic and anti-tuberculosis therapy was not helpful. Laboratory examination of sputum indicated the causative agent was Nocardia. Key words: Pulmonary nocardiosis, kidney transplantation
Keywords: Pulmonary nocardiosis; kidney transplantation